Analisis Rantai Nilai Komoditas Kubis (Brassica oleracea. L) di Kabupaten Karo Sumatera Utara (Pemetaan Aktor, Margin Pemasaran, dan Nilai Tambah) - Lory Br Ginting Munthe; Erlyna Wida Riptanti; Agustono Agustono (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Indonesia is known as an agricultural country whose economy relies on the agriculture, forestry and fisheries sectors which are one of the dominant sectors in people's income. The agriculture, forestry and fisheries sectors directly affect the existence or absence of equitable development so that development needs to be increased in order to meet food needs and domestic industrial needs, increase production results, and expand employment opportunities. Increasing development in the agriculture, forestry and fisheries sectors has experienced many problems that are challenges for many countries. These problems can be overcome by utilizing agribusiness efforts, especially in the horticulture sector. Karo Regency is one of the centers of horticulture production, especially cabbage which has excellent potential to be developed. The high demand for cabbage at home and abroad is often faced with various problems such as marketing channels that are too long, a value chain that is not yet optimal, unstable cabbage prices and limited market access. This study aims to determine the cabbage value chain, determine the value of cabbage farmer's share, and improvement strategies (upgrading) in the cabbage value chain in Karo Regency, North Sumatra. The basic method of research is descriptive analytic. The method of determining the research location was carried out purposively in three sub-districts in Karo Regency which have the highest cabbage production, namely Simpang Empat Sub-district, Naman Teran Sub-district and Merek Sub-district. The method of determining the sample of farmers and marketing institutions was carried out using purposive sampling and snowball sampling techniques so that 60 farmers were obtained, two village collectors, three sub-district collectors, three retailers, 13 wholesalers and five exporters. The data used in this study include primary data and secondary data. Interviews, observations, and documentation carried out data collection methods. The data analysis methods used were value chain analysis, cost analysis, profit, margin and marketing efficiency, and upgrading value chain.